Investigating the Influence of Stereotypes on Female Students' Enrollment in Motor Vehicle Mechanic Work in Gombe State: Gender Bias and Career Aspirations - Kumazhege, Stephen Z.; Umar, Hadiza; Ibanga, Isaac John (The Indonesian Institute of Science and Technology Research, 2024)
This study addresses the persistent underrepresentation of female students in non-traditional vocational trades, specifically Motor Vehicle Mechanic Work, within Gombe State Technical Colleges. The total population for this study was 527 including administrators, teachers and parents of Motor Vehicle Mechanic Work trade students in Government Science and Technical Colleges in Gombe State. The sample size of the study was 116 determined using stratified random sampling. The study employed a descriptive survey research design, focusing on Gombe State in Nigeria, where seven Government Science and Technical Colleges were selected for the research. Three research questions and hypotheses guided the study. Data was collected through a researcher-developed structured questionnaire, and statistical methods including means, standard deviations, and ANOVA were used to analyze the data. Findings of the study indicated that parental influence, including preferences for preferred courses and concerns about safety, significantly influenced female students' enrollment in Motor Vehicle Mechanic Work. Peer group dynamics, such as imitation, aspirations, and subject choice, also played a role in shaping female students' decisions. Cultural factors, including perceptions of education, domestic roles, early marriage, and societal support, further influenced their choices. Interestingly, the study revealed a convergence of perspectives among Motor Vehicle Mechanic Works Trade teachers, school administrators, and parents regarding the identified influences. Recommendations stemming from these findings include targeted awareness campaigns for parents, peer mentorship programs, and collaborations with local leaders and institutions to challenge and reshape cultural norms that discourage female participation in non-traditional trades.